Use of Emergency Department Extracorporeal Membrane Oxygenation for Treatment of Acute Necrotizing Myocarditis - Loner, Carly A. (Clin Pract Cases Emerg Med, 2019)
We report a case of acute necrotizing eosinophilic myocarditis (ANEM) secondary to drug rash with eosinophilia and systemic symptoms (DRESS) related to administration of minocycline. Myocarditis is a rare complication of DRESS and can manifest as either a self-limited hypersensitivity myocarditis or as the frequently fatal ANEM. Due to the high morbidity and mortality caused by this disease, emergency physicians should be aware of the potential of ANEM in patients with history of DRESS and new-onset cardiac dysfunction. This case reviews the clinical presentation and management of ANEM and the potential role of extracorporeal membrane oxygenation use in the emergency department.